Involvement of iNKT Cells In Bronchial Asthma - Kandari, Swarnima; ., Ratnakar; Chandola, Abhishek (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: Bronchial asthma is a prevalent inflammatory disease characterized by infiltration with eosinophils, lymphocytes, and mast cells in the airway leading to airway hypersensitivity and increased mucus secretion. T helper (Th) 2-based immune responses drive the inflammatory process. Numerous mechanisms are being studied to understand the progression of allergen induce asthma which subsequently led to the identification of a new population of T cells called the iNKT cells which showed promising results when experimented on murine models. iNKT cells are potent immune modulators involved in a variety of immunoregulations. This potency is the result of their ability to produce prime Th2 cytokines. The recognition of lipid antigens is required for the activation of iNKT cells. When an inflammation occurs due to Th2 cells and ozone, endogenous glycolipids become modified. This causes the activation of various subsets of iNKT cells and initiates airway hyperactivity. Infrequent human studies depict that the number of iNKT cells in BAL fluid ranges from 1 % of lung lymphocytes to 14 % which is a sign of dynamic fluctuation in the number of iNKT cells. Methods: Selective literature review including primary and secondary sources of literature. Eg. Cochrane database, NCBI, MEDLINE database.